The role of instructional quality on online learning intentions of university students: The technology acceptance model of Zoom - Tuti Iriani; Prastiti Laras Nugraheni (Institute of Advanced Engineering and Science, 2023)
E-learning technology has a vital role to play in supporting the realization of learning goals during the COVID-19 pandemic. One that is often used is video conferencing technology from Zoom. Many studies have discussed the important role of e-learning technology, but there are still limited studies that examine how the role of Zoom technology in increasing student engagement in online learning. Thus, this study focuses to reveal the impact of online instructional quality using Zoom video conferencing technology on increasing students’ online learning intentions. We use the technology acceptance model (TAM) approach to answer the objectives of this study. This study randomly involved 190 students at Universitas Negeri Jakarta, Indonesia through an online questionnaire. We used structural equation modeling (SEM) analysis to examine the effect on each variable. In addition, we also use a bootstrap confidence interval estimate to investigate the role of mediation. The study results reveal that students' online learning intentions are influenced by perceived usefulness and ease of using Zoom. Also, perceived usefulness and ease of use are proven to mediate the effect of instructional quality on students’ online learning intentions using Zoom video conferencing technology. The results of this study provide important implications for education practitioners to develop engaging online learning for students.